JURNALISME WARGA DALAM LINGKARAN DAN CENGKERAMAN MEDIA ARUS UTAMA: Studi Kasus Kompasiana.com dan Pasangmata.com - Muttaqin, Umar Imamul (Journal Communication Spectrum : Capturing New Perspectives in Communication, 2015)
The new media (internet) and the emergence of the citizen journalism movement presented new trends in the society, including writing through the blog. Journalistic activities by citizen journalists apparently attracted online mainstream media. This article presents the application of citizen journalism by mainstream online media and investigates how the citizen media used as a tool for personal gain. Using political economy media theory by Vincent Mosco that includes commodification, spatialization, and structuration, this article focuses on studying  Kompasiana.com and Pasangmata.com as a result of vertical integration (and expansion of) online mainstream media Kompas.com and Detik.com. The results indicate that citizen journalists embraced by the mainstream online media deemed to the economic interests of the media owner that is closely related to expanding the area of profit gain.  Citizen journalists considered in this study has been used as a commodity by the mainstream media and advertisers. To cite this article (7th APA style): Muttaqin, U. I. (2015). Jurnalisme Warga dalam Lingkaran dan Cengkeraman Media Arus Utama: Studi Kasus Kompasiana.com dan Pasangmata.com [Citizen Journalism in the Circles and Grips of Mainstream Media]. Journal Communication Spectrum, 5(2), 86-100